2008
DOI: 10.4067/s0716-10182008000500009
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis: Espoligotipos en el Estado Carabobo, Venezuela

Abstract: In order to study the genetic variability of Mycobacterium tuberculosis circulating in the Carabobo State at Venezuela, 317 strains of M. tuberculosis isolated from patients living in different health districts whose acid fast smears were positive, were included. Each strain was characterized by spoligotyping and the pattern compared with the national and worldwide SpolDB4.0 databases; 220 isolates (69.4%) were grouped in 24 clusters, being LAM the most common family (34%). In contrast to other Venezuelan regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…However it was much younger, 32.6 years, for patients from the indigenous Delta Amacuro region. Also, while males made up about 71% of patients from Caracas, 70% from Carabobo (69%) [ 20 ], and 64% from Amazonas [ 19 ], males comprised only 54% of the patients from Delta Amacuro [ 21 ]. Surprisingly, female patients had significantly lower mean ages overall, and also in Caracas and in Delta Amacuro (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However it was much younger, 32.6 years, for patients from the indigenous Delta Amacuro region. Also, while males made up about 71% of patients from Caracas, 70% from Carabobo (69%) [ 20 ], and 64% from Amazonas [ 19 ], males comprised only 54% of the patients from Delta Amacuro [ 21 ]. Surprisingly, female patients had significantly lower mean ages overall, and also in Caracas and in Delta Amacuro (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It includes large numbers of isolates from the two biggest cities in the center of the country – Caracas and Valencia, as well as from two rural, largely Amerindian populations – Delta Amacuro and Amazonas, located at widely separated geographical poles, and also a smaller number of isolates from other regions (Figure 1 and Additional file 1 ). Data on strains from the Amazonas [ 19 ], Carabobo [ 20 ], and Delta Amacuro [ 21 ] states that have been described separately but are included here in a broader, national analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Isolates with the genotype SIT863 were reported in three earlier studies carried out in Porto Alegre, the first reported by Cafrune et al (41) (43,44). At SITVITWEB, four cases were reported, and three of these were isolated in Pelotas (Rio Grande do Sul, Brazil) but without information about the isolation data; the other case was isolated in the United States in 2003.…”
Section: Discussionmentioning
confidence: 97%
“…This spoligopattern is not often reported. One isolate was found in the United States of America, two were found in the city of Pelotas, RS and, more recently, two were found in Venezuela (Borsuk et al 2005, Sequera et al 2008). However, SIT729 was reported to be associated with incarceration by Cafrune (2009); 72% of the patients with this SIT were inmates.…”
Section: Discussionmentioning
confidence: 99%